If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(w + 1) = 9w + 11 Reorder the terms: 7(1 + w) = 9w + 11 (1 * 7 + w * 7) = 9w + 11 (7 + 7w) = 9w + 11 Reorder the terms: 7 + 7w = 11 + 9w Solving 7 + 7w = 11 + 9w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-9w' to each side of the equation. 7 + 7w + -9w = 11 + 9w + -9w Combine like terms: 7w + -9w = -2w 7 + -2w = 11 + 9w + -9w Combine like terms: 9w + -9w = 0 7 + -2w = 11 + 0 7 + -2w = 11 Add '-7' to each side of the equation. 7 + -7 + -2w = 11 + -7 Combine like terms: 7 + -7 = 0 0 + -2w = 11 + -7 -2w = 11 + -7 Combine like terms: 11 + -7 = 4 -2w = 4 Divide each side by '-2'. w = -2 Simplifying w = -2
| d/-2=2 | | -(y+5)+2y-11=-26 | | 4w+48=-2(w-9) | | -10.5-9.7=2w+1.4-1w | | 3(x+8)=63 | | 5p-4p+2p+3=12 | | 9^3X-1=1/27 | | 8t=-8 | | x^3+x=500 | | -10h=-20 | | 2/12=6/x | | 15w+-19w=-16 | | W/2-3^12 | | tg(-x)=1-2tg(x) | | cos(240)= | | x(13+x)=0 | | (3-i)(x-iy)=3-11i | | x+y=1.70 | | 12(x-4)-8(2x-7)=3(x+5) | | 3+10x=0.5 | | 7(v-4)=3v-4 | | 11x-54-8x-12=7x+30-6x | | 5u-43=9(u-7) | | 2(u+7)=-2u+30 | | 1.1(-0.3w+10)=7.7 | | 3=3(v+5)+3v | | p=2(3)+2(4) | | -6x+4(x-8)=-24 | | -4(3y)-5+3(5y+5)= | | -7w+3(w+8)=16 | | 8-2y=-4y | | -97+12y+4=5(4y-3)-6 |